Umbilical cord blood IL-6 as predictor of early-onset neonatal sepsis in women with preterm prelabour rupture of membranes - Cobo Teresa; Kacerovský, Marian; Andrýs, Ctirad; Drahošová, Marcela; Kacerovská Musilová, Ivana; Hornychová, Helena; Jacobsson Bo (PLoS One, 2013)
OBJECTIVE: To evaluate umbilical cord interleukin (IL)-6 and funisitis as independent predictors of early-onset neonatal sepsis (EONS) in preterm prelabor rupture of membranes (PPROM). DESIGN: Prospective cohort study. SETTING: Evaluation of umbilical cord IL-6 and funisitis as predictors of early-onset neonatal sepsis in PPROM. POPULATION: 176 women with PPROM between 23+0-36+6 weeks of gestation. METHODS: Umbilical cord IL-6 was assayed by ELISA. Funisitis was defined according to the Salafia classification. Data was adjusted by gestational age at delivery and prenatal administration of corticosteroids and antibiotics. MAIN OUTCOME MEASURES: Binary logistic regression was performed to assess the independence of umbilical cord IL-6 and funisitis to predict EONS in women complicated with PPROM. RESULTS: The rate of EONS was 7%. Funisitis was present in 18% of women. Umbilical cord IL-6 was significantly higher in women complicated with EONS than without [median (range) 389.5 pg/mL (13.9-734.8) vs 5.2 (0.1-801-4), p<0.001]. Umbilical cord IL-6 was the only independent predictor of early-onset neonatal sepsis (odds ratio 13.6, p = 0.004). CONCLUSION: Umbilical cord IL-6 was the only predictor of early-onset neonatal sepsis in PPROM. Contrary to what is reported, funisitis was not.
Keywords: těhotenství; Interleukin-6; fetální krev; lidé; Sepsis; Adult; předčasný odtok plodové vody; sepse; ELISA; prospektivní studie; Female; Enzyme-Linked Immunosorbent Assay; Humans; Infant, Newborn; interleukin-6; Prospective Studies; Fetal Membranes, Premature Rupture; chorioamnionitida; mladý dospělý; novorozenec; Pregnancy; ženské pohlaví; Young Adult; Chorioamnionitis; dospělí; Fetal Blood